The high Andes, gene flow and a stable hybrid zone shape the genetic structure of a wide-ranging South American parrot - Masello, Juan F.; Quillfeldt, Petra; Munimanda, Gopi K.; Klauke, Nadine; Segelbacher, Gernot; Schaefer, H. Martin; Failla, Mauricio; Cortés, Maritza; Moodley, Yoshan; Justus Liebig University Giessen (My University, 2011)
Background: While the gene flow in some organisms is strongly affected by physical barriers and geographical distance, other highly mobile species are able to overcome such constraints. In southern South America, the Andes (here up to 6,900 m) may constitute a formidable barrier to dispersal. In addition, this region was affected by cycles of intercalating arid/moist periods during the Upper/Late Pleistocene and Holocene. These factors may have been crucial in driving the phylogeographic structure of the vertebrate fauna of the region. Here we test these hypotheses in the burrowing parrot Cyanoliseus patagonus (Aves, Psittaciformes) across its wide distributional range in Chile and Argentina. Results: Our data show a Chilean origin for this species, with a single migration event across the Andes during the Upper/Late Pleistocene, which gave rise to all extant Argentinean mitochondrial lineages. Analyses suggest a complex population structure for burrowing parrots in Argentina, which includes a hybrid zone that has remained stable for several thousand years. Within this zone, introgression by expanding haplotypes has resulted in the evolution of an intermediate phenotype. Multivariate regressions show that present day climatic variables have a strong influence on the distribution of genetic heterogeneity, accounting for almost half of the variation in the data. Conclusions: Here we show how huge barriers like the Andes and the regional environmental conditions imposed constraints on the ability of a parrot species to colonise new habitats, affecting the way in which populations diverged and thus, genetic structure. When contact between divergent populations was re-established, a stable hybrid zone was formed, functioning as a channel for genetic exchange between populations.
Keywords: ddc:570; ddc:590